THE EFFECT OF Thieleria lestoquardi ON THE AGE OF PUBERTY IN EXPERIMENTALLY INFECTED DESERT LAMB EWES - A.A., Aisha; Y.H., Elmansoury; H.S., Abdalla; E.B., Amna; A.A., Azza; A. A., Tahani; S.H., Eisa; E.A., Babeker (Journal of Veterinary Medicine and Animal Production, 2021)
The study aimed to investigate the effect of T. lestoquardi infection on reaching puberty in kid ewes and also reflect the biochemical picture in the serum of experimentally infected kid ewes. Twenty (20) Sudanese desert lamb ewes (2-3 year age) were divided into two groups of ten each. Group (1) received infection with T. lestoquardi group (2) remained as an uninfected group. A significant delay (4-6 months) in reaching puberty in desert lamb ewes were noticed in the infected group. There was also an irregular estrus cycles appear in the progesterone profiles of the infected lamb ewes. There is a decrease in serum total protein, serum albumin and serum globulin values. However, at the same period, there was an increase in serum urea and serum creatinine values in the infected group